Excitation of Kerr quasinormal modes in extreme-mass-ratio inspirals - Jonathan Thornburg; Barry Wardell; Maarten van de Meent (Physical Review Research, 2020)
If a small compact object orbits a black hole, it is known that it can excite the black hole's quasinormal modes (QNMs), leading to high-frequency oscillations (“wiggles”) in the radiated field at J^{+}, and in the radiation-reaction self-force acting on the object after its orbit passes through periapsis. Here we survey the phenomenology of these wiggles across a range of black hole spins and equatorial orbits. In both the scalar-field and gravitational cases, we find that wiggles are a generic feature across a wide range of parameter space, and they are observable in field perturbations at fixed spatial positions, in the self-force, and in radiated fields at J^{+}. For a given charge or mass of the small body, the QNM excitations have the highest amplitudes for systems with a highly spinning central black hole, a prograde orbit with high eccentricity, and an orbital periapsis close to the light ring. However, the QNM amplitudes remain nonzero for all black hole spins and for retrograde as well as for prograde orbits. The QNM amplitudes depend smoothly on the orbital parameters, with only very small amplitude changes when the orbit (discrete) frequency spectrum is tuned to match QNM frequencies. The association of wiggles with QNM excitations suggests that they represent a situation where the nonlocal nature of the self-force is particularly apparent, with the wiggles arising as a result of QNM excitation by the compact object near periapsis, and then encountered later in the orbit. Astrophysically, the effects of wiggles at J^{+} might allow direct observation of Kerr QNMs in extreme-mass-ratio inspiral (EMRI) binary black hole systems, potentially enabling new tests of general relativity.